A New Route to Obtain Perfluorodecalin Nanocapsules as An Oxygen Carrier in Cosmetic Formulations - Svarc, Federico (2018)
The preparation of Perfluorodecalin (PFD) encapsulated silica nanocapsules via a two-step process method using a combination of emulsifiers ( Pluronic 127, purified Soy Lecithin and Polysorbate 80 ) to obtain first stabilized water nanoemulsions of PFD as a template, followed by ?in situ? precipitation of silica is demonstrated herein. Our method differs from previously published sol-gel processes starting from TEOS (Tetraethyl Orthosilicate) or TMOS (Tetramethyl Orthosilicate) because Sodium Silicate was used as departing material, hydrolyzed under strictly controlled conditions aswe describe in what follows. To obtain uniform sized nanocapsules we found essential to slow down the hydrolytic process, controlling the temperature, pH and ionic strength. Successful incorporation of PDF (20% wt) into the silica nanocapsule core was evident from EDAX analysis. Our aim was to propose PFD charged nano-silica carriers as a new approach to topical treatment of aging skin due to intrinsic instability of perfluorocarbon emulsions.